Acceptability of a Tenofovir Disoproxil Fumarate Intravaginal Ring for HIV Pre-Exposure Prophylaxis Among Sexually Active Women. Issue 12 (December 2020) - Dobkin, April; McWalters, Jessica; Barnett, Rebecca; Ray, Laurie L.; Espinoza, Lilia; McGinn, Aileen P.; Atrio, Jessica M.; Keller, Marla J.
Abstract : Introduction: Vaginal ring delivery of antiretroviral drugs may provide protection against acquisition of HIV-1 when used as Pre-Exposure prophylaxis. As part of a randomized placebo-controlled safety trial of a tenofovir disoproxil fumarate (TDF) intravaginal ring (IVR), we assessed product acceptability through surveys of women after continuous ring use. Methods: Sexually active, HIV-negative women were enrolled to investigate the safety and pharmacokinetics of 3 months of continuous TDF IVR use. The study was designed to include 40 US participants randomly assigned (3:1) to a TDF or placebo IVR. Twelve were randomized to TDF and 5 to the placebo group before the study was electively discontinued because of the development of vaginal ulcerations in 8 women in the TDF group. Acceptability data were gathered via self-administered, computer-based questionnaires. Results: The average age of the 17 participants was 31 years (range, 18–42 years). Sixteen participants (94%) completed all questions at 2 study visits. When asked about ring likeability after 1 month of ring use, 12 (75%) of 16 reported overall liking the ring, including 6 (75%) of 8 who developed ulcerations. In addition, 10 (83%) of 12 who had their menses during the first month of ring use were not bothered by the ring, and 11 (69%) of 16 stated that the ring was not bothersome with use during sex. Conclusions: Despite unanticipated ulcers, TDF and placebo IVRs were acceptable to some women, even when used with menses and during sex, which is promising for continued development of IVRs for HIV prevention. Abstract : We report acceptability data from a safety trial of a tenofovir disoproxil fumarate intravaginal ring. The trial ended early because vaginal ulcers developed in 8 tenofovir disoproxil fumarate intravaginal ring users.